TEKNIK DAN SRATEGI KONSELING KELOMPOK - Sigit Sanyata (Paradigma, 2010)
Group counseling is one kind of counseling service strategies. The difference concept of both group counseling and individual is that the group counseling emphasizes toward social interaction of the members. The group counseling discuses integrated approach which combines group dynamic interaction and counselors’ personal competencies. The goal of group counseling is to change the group behavior members based on that group interaction. The group processes are applied for children group teenagers, adults and elderlyadapted to their development characteristics.Keywords: counseling, groups counseling